2015
DOI: 10.1098/rstb.2014.0276
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad and the ugly of marine reserves for fishery yields

Abstract: One contribution of 16 to a theme issue 'Measuring the difference made by protected areas: methods, applications and implications for policy and practice'. The good, the bad and the ugly of marine reserves for fishery yields Marine reserves (MRs) are used worldwide as a means of conserving biodiversity and protecting depleted populations. Despite major investments in MRs, their environmental and social benefits have proven difficult to demonstrate and are still debated. Clear expectations of the possible outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…When scaled to the proper size or combined as an interconnected network, they can effectively protect fisheries stocks and increase fisheries yields [13]. Yet, to be successful for both conservation and fisheries goals, MPA designs must adequately address the consequences of species movement, including swimming behavior of adults and dispersal of larvae [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When scaled to the proper size or combined as an interconnected network, they can effectively protect fisheries stocks and increase fisheries yields [13]. Yet, to be successful for both conservation and fisheries goals, MPA designs must adequately address the consequences of species movement, including swimming behavior of adults and dispersal of larvae [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies suggest that a well-designed MPA can provide comparable benefits to those obtained with perfect management of the catch or they can even exceeded under the right conditions [3]. For example, Hasting and Botsford [6] showed that for species with sedentary adults and larval dispersal, the optimal MPA size can offer identical stock protection and yields to those provided by the optimal fishing mortality rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, achieving an integration of retrospective and prospective impact studies in a unified scientific architecture will take substantial communication and collaboration among evaluators, planners and modellers. Initial steps towards this integration are outlined in three articles in this issue [20][21][22].…”
Section: (C) Predicting Impacts In Novel Contextsmentioning
confidence: 99%
“…When we attempt to isolate the effects of protected areas on ecological indicators, we must disentangle the effects caused by protected areas from the effects caused by the productivity of the landscapes or seascapes that are typically protected. In both retrospective and prospective studies, the answers to the question about selection identify moderators and mechanisms of protected area impacts (see [17,[19][20][21]23]). The ways in which these factors shape impacts must be elucidated if we are to have a sound evidence base for guiding protected area management.…”
Section: Challenges Addressed By Articles In This Issue (A) Counterfamentioning
confidence: 99%